A Robust Predictive Current Controller for PMSM Drives - Turker, Turker; Buyukkeles, Umit; Bakan, A. Faruk (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2016)
High-performance current control is required to obtain a smooth output torque in permanent-magnet synchronous motor (PMSM) drives. In this manner, a new discrete-time robust predictive current controller is presented for PMSM drives. Controller and current prediction schemes are designed based on the dead-beat structure. The dead-beat control has good transient response, but it suffers from parametric uncertainties and unmodeled dynamics. In order to provide robustness, a discrete-time integral term is added to the dead-beat current prediction. The stability analysis is carried out considering the prediction error dynamics, nonlinear uncertain model of PMSM, and the integral action as the states of the overall system. The designed robust predictive controller is tested through numerical simulations and experiments. The proposed controller is easy to implement and suitable for high-performance PMSM applications.
Keywords: Dead-beat current control; digital current control; permanent-magnet synchronous motor (PMSM); robust prediction; TORQUE RIPPLE MINIMIZATION; CURRENT-CONTROL SCHEME; INTERNAL-MODEL; MOTOR-DRIVES; VOLTAGE; PWM; IMPLEMENTATION; DESIGN; Automation & Control Systems; Engineering; Instruments & Instrumentation